2021
DOI: 10.1021/acs.jpcc.1c06497
|View full text |Cite
|
Sign up to set email alerts
|

Superhalogen Boron Tetrafluoride Surface Modification Reduces the Formation of Organic Cation Vacancies on the Surface of Halide Perovskite Films

Abstract: It is generally known that lead halide perovskite films used in solar cell devices inevitably introduce defects during solution-based growth at near room temperature. In all defects, the halide anion and organic cation vacancies are ubiquitous, facilitating ion diffusion and leading to the decomposition of thin films at the surface and grain boundaries. Studies have shown that fluoride can be introduced into the film and the strong electronegativity of fluorine can be used to passivate the point vacancies. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In order to stabilize the α-phase, cation substitutions have been widely investigated. ,, Anion substitution is another way to tune the stability of the phase. Recently, molecular monovalent anions, called pseudo-halides, have been used as additives to the perovskite phase. , For example, Jeong et al and Hui et al reported the stabilization of α-FAPbI 3 thin films by adding formate anion (HCOO – ). , BF 4 – with high electronegativity has been reported theoretically to increase the surface vacancy formation energy, leading to passivation against halide defects . Lu et al reported that CH 3 NH 3 SCN vapor treatment of FAPbI 3 thin films to introduce the thiocyanate anion SCN – stabilizes the α-phase .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to stabilize the α-phase, cation substitutions have been widely investigated. ,, Anion substitution is another way to tune the stability of the phase. Recently, molecular monovalent anions, called pseudo-halides, have been used as additives to the perovskite phase. , For example, Jeong et al and Hui et al reported the stabilization of α-FAPbI 3 thin films by adding formate anion (HCOO – ). , BF 4 – with high electronegativity has been reported theoretically to increase the surface vacancy formation energy, leading to passivation against halide defects . Lu et al reported that CH 3 NH 3 SCN vapor treatment of FAPbI 3 thin films to introduce the thiocyanate anion SCN – stabilizes the α-phase .…”
Section: Introductionmentioning
confidence: 99%
“…25,26 BF 4 − with high electronegativity has been reported theoretically to increase the surface vacancy formation energy, leading to passivation against halide defects. 27 Lu et al reported that CH 3 NH 3 SCN vapor treatment of FAPbI 3 thin films to introduce the thiocyanate anion SCN − stabilizes the αphase. 28 Using molecular dynamics simulations, they demonstrated that the partial replacement of surface anions from I − to SCN − promotes the δ-to-α transition.…”
Section: ■ Introductionmentioning
confidence: 99%
“…41,42 The addition of BF 4 À in FAPbI 3 could enhance the formation energy of FA + -related vacancies to improve the structural stability. 42 BF 4 À has a higher electronegativity than the F À , implying that the bonding between BF 4 À and its neighboring Pb atom would be more ionic. Li et al calculated the VBM and CBM of the minimumenergy superlattice structures of (FAPbI 3 ) 3 /CsPbI 2 BF 4 , (MAPbI 3 ) 3 /CsPbI 2 BF 4 , (FAPbI 3 ) 3 /MAPbI 2 BF 4 , and (CsPbI 3 ) 3 / MAPbI 2 BF 4 (Fig.…”
Section: Superhalogensmentioning
confidence: 99%
“…40 BF 4 − and PF 6 − could partially substitute I − to form stable organic–inorganic perovskite superlattices, which provide a large variety of possibility to expand the possible perovskite formulations. 41,42 The addition of BF 4 − in FAPbI 3 could enhance the formation energy of FA + -related vacancies to improve the structural stability. 42 BF 4 − has a higher electronegativity than the F − , implying that the bonding between BF 4 − and its neighboring Pb atom would be more ionic.…”
Section: Overview Of Nonhalide Anionsmentioning
confidence: 99%
“…32 Yang et al reported that the BF 4 − anion not only passivates the iodine vacancy but also increases the formation energy of the FA vacancy due to its large electronegativity based on DFT calculations. 33 Furthermore, doping perovskites with tetrauoroborate results in a more n-type characteristic, which facilitates electron transport to the ETL. [34][35][36] For example, Su et al reported that perovskite lms with BF 4 exhibited stronger n-type conductivity than the reference based on ultraviolet photoelectron spectroscopy (UPS) measurement.…”
Section: Introductionmentioning
confidence: 99%